On the efficiency of slit-check dams in retaining granular flows. Issue 3 (4th April 2019) - Marchelli, Maddalena; Leonardi, Alessandro; Pirulli, Marina; Scavia, Claudio
Abstract : Retention barriers are a common countermeasure for mitigating the hazards associated with debris flows. With the aim to regulate sediment transport and retain large boulders, which have the potential to be highly destructive, openings are nowadays embedded in the barrier body. The rational design of the size and spacing of these outlets is a non-trivial, and still open, issue. Nevertheless, its solution is necessary in order to control the clogging process and consequently guarantee the effectiveness and efficiency of the barrier. In this paper, an enhanced numerical model, based on the discrete-element method, is presented, validated and proposed to analyse the interaction between dry, granular flows and barriers with a single outlet (slit-check dams). The lower and upper values of the outlet size that causes clogging of the outlet are identified. These are found to be a function of the channel inclination and the frictional properties of the grains. There is a range of outlet sizes that promotes slow and progressive clogging. The conditions necessary for this condition to occur are determined. This allows the barrier to perform an energy-breaking function for a longer time and requires less maintenance after a debris flow event.